Investigation of the Relationship between Novel Coronavirus (COVID-19) Anxiety and Mental Toughness in Professional Volleyball Players - Ebru Şenel; Burkay Cevahircioğlu (Journal of Educational Issues, 2024)
In the study, the relationship between anxiety about catching the new type of coronavirus (COVID-19) and mental resilience in professional volleyball players was examined. This study is in the descriptive survey model, which is one of the quantitative research methods. The study was carried out with a total of 209 athletes, 145 females and 64 males, who are within the scope of the 1st league clubs of the Turkish Volleyball Federation (TVF). The data were collected with the “Anxiety Scale of Catching a New Type of Coronavirus” developed by Demir et al (2020) and the “Mental Endurance Inventory in Sports” developed by Sheard et al (2009) and adapted into Turkish by Altıntaş and Koruç (2016). The collected data were analyzed with the Skewness and Kurtosis test, and as a result of the examination, it was determined that the data showed a normal distribution. Student T-Test and One-Way Analysis of Variance (ANOVA) tests, which are parametric tests, were used in the analysis of the data. Pearson Correlation Analysis was used to examine the relationship between athletes’ anxiety about catching the new type of coronavirus and their mental toughness. SPSS 21.0 statistical package program was used for all statistical analyzes and statistical significance level was taken as p < 0.05 in all analyzes. According to the results of the analysis, there is a statistical significance between the anxiety of the athletes about catching the new type of coronavirus and the age variable. A statistically significant difference was found between the mental endurance levels of the athletes and the variables of gender, age, monthly income and weekly training number. According to the results of the correlation analysis, a statistically significant relationship was not determined between the anxiety of catching the new type of coronavirus and the mental endurance characteristics of the athletes. A negative and low-level significant relationship was found between the individual anxiety values of the athletes and their control scores. As a result, it was determined that professional volleyball players’ anxiety about catching a new type of coronavirus was not related to their mental toughness levels, but the athletes’ individual anxieties were related to their control levels. In this regard, it is recommended that professional athletes receive mental support in order to keep their anxiety levels under control during the coronavirus process.